1997
DOI: 10.1523/jneurosci.17-03-01004.1997
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Amyloid β-Protein Precursor Colocalizes with β1 Integrins at Substrate Contact Sites in Neural Cells

Abstract: Amyloid ␤-protein (A␤), the principal constituent of the senile plaques seen in Alzheimer's disease (AD), is derived by proteolysis from the ␤-amyloid precursor protein (␤PP). The distribution and trafficking of cell surface ␤PP are of particular interest because some of these molecules are direct precursors of secreted A␤ and because the localization of ␤PP at the cell surface may be related directly to its physiological functions. Recently, we reported that, in cultured hippocampal neurons, cell surface ␤PP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
103
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(109 citation statements)
references
References 47 publications
6
103
0
Order By: Relevance
“…Treatment of primary cortical neurons with Ab results in FAK activation (Williamson et al, 2002), and aberrant activation of focal adhesion proteins mediates Ab-induced neuronal dystrophy (Grace et al, 2002;Williamson et al, 2002). In addition, APP, a potential receptor for Ab (Lorenzo et al, 2000), is found at focal contacts (Sabo et al, 2001); it colocalizes with b1 integrins in neuronal cells (Yamazaki et al, 1997), and antibody-mediated clustering of APP induces significant loss of dendritic spines (Lefort et al, 2012) and neuronal injury through FAK activation (Xu et al, 2009). We found that clustering of APP was sufficient to induce Glu MTs and both APP and caspase-2 expression were required for the formation of stable Glu MTs by Ab, suggesting that induction of MT stability by Ab is initiated by the same APP/ caspase-2/RhoA pathway that leads to neurotoxicity by Ab in neurons (Lefort et al, 2012;Pozueta et al, 2013;Troy et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of primary cortical neurons with Ab results in FAK activation (Williamson et al, 2002), and aberrant activation of focal adhesion proteins mediates Ab-induced neuronal dystrophy (Grace et al, 2002;Williamson et al, 2002). In addition, APP, a potential receptor for Ab (Lorenzo et al, 2000), is found at focal contacts (Sabo et al, 2001); it colocalizes with b1 integrins in neuronal cells (Yamazaki et al, 1997), and antibody-mediated clustering of APP induces significant loss of dendritic spines (Lefort et al, 2012) and neuronal injury through FAK activation (Xu et al, 2009). We found that clustering of APP was sufficient to induce Glu MTs and both APP and caspase-2 expression were required for the formation of stable Glu MTs by Ab, suggesting that induction of MT stability by Ab is initiated by the same APP/ caspase-2/RhoA pathway that leads to neurotoxicity by Ab in neurons (Lefort et al, 2012;Pozueta et al, 2013;Troy et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Given the direct involvement of APP with both cell adhesion and neuronal injury by Ab (Sabo et al, 2001;Xu et al, 2009;Yamazaki et al, 1997), we tested whether stimulation of APP signaling was also required to induce stable Glu MTs by Ab. Interestingly, downregulation of APP expression prior to Ab treatment completely abrogated the induction of stable Glu MTs by Ab (Fig.…”
Section: App Signaling Is Required For Ab Induction Of Glu Mtsmentioning
confidence: 99%
“…Several membrane proteins have been shown to participate in A␤-induced apoptosis ; in contrast, A␤PP and/or integrins could be the main cell-surface candidates for A␤ fibril-induced neuronal dystrophy. Both A␤PP and integrins participate in mechanisms of neuronal plasticity (Breen et al, 1991;Perez et al, 1997;Benson et al, 2000;Sabo et al 2001a), bind to A␤ fibrils (Sabo et al, 1995;Lorenzo et al, 2000;Van Nostrand et al, 2002), colocalize in adhesion sites (Storey et al, 1996;Yamazaki et al, 1997), and cluster around A␤ deposits in aberrant focal adhesion structures (Grace and Busciglio, 2003;Heredia et al, 2004). In fact, A␤ dystrophy requires aberrant activation of focal adhesion proteins, including Paxillin (Grace and Busciglio, 2003), activation of which could also depend on A␤PP or integrins, through their interaction with different cytoplasmic proteins (Sabo et al, 2001b;Zambrano et al, 2001;Martin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…4 However, integrin-mediated death is similar to apoptosis induced by the b-amyloid precursor protein (APP), a dependence receptor which initiates apoptosis via activation of caspase 8 69 and also happens to associate with integrins at sites of ECM contact. 70 Interestingly, substrate-ECM contact may also prevent apoptosis induced by APP.…”
Section: Unligated Integrins Recruit Caspasementioning
confidence: 99%